MiR‐146b Protects the Perinatal Brain against Microglia‐Induced Hypomyelination. Issue 1 (26th November 2021) - Bokobza, Cindy; Joshi, Pooja; Schang, Anne‐Laure; Csaba, Zsolt; Faivre, Valérie; Montané, Amélie; Galland, Anne; Benmamar‐Badel, Anouk; Bosher, Emmanuelle; Lebon, Sophie; Schwendimann, Leslie; Mani, Shyamala; et al.
Abstract : Objectives: In the premature newborn, perinatal inflammation mediated by microglia contributes significantly to neurodevelopmental injuries including white matter injury (WMI). Brain inflammation alters development through neuroinflammatory processes mediated by activation of homeostatic microglia toward a pro‐inflammatory and neurotoxic phenotype. Investigating immune regulators of microglial activation is crucial to find effective strategies to prevent and treat WMI. Methods: Ex vivo microglial cultures and a mouse model of WMI induced by perinatal inflammation (interleukin‐1‐beta [IL‐1β] and postnatal days 1–5) were used to uncover and elucidate the role of microRNA‐146b‐5p in microglial activation and WMI. Results: A specific reduction in vivo in microglia of Dicer, a protein required for microRNAs maturation, reduces pro‐inflammatory activation of microglia and prevents hypomyelination in our model of WMI. Microglial miRNome analysis in the WMI model identified miRNA‐146b‐5p as a candidate modulator of microglial activation. Ex vivo microglial cell culture treated with the pro‐inflammatory stimulus lipopolysaccharide (LPS) led to overexpression of immunomodulatory miRNA‐146b‐5p but its drastic reduction in the microglial extracellular vesicles (EVs). To increase miRNA‐146b‐5p expression, we used a 3DNA nanocarrier to deliver synthetic miRNA‐146b‐5p specifically to microglia. Enhancing microglial miRNA‐146b‐5p overexpression significantly decreased LPS‐induced activation, downregulated IRAK1, and restored miRNA‐146b‐5p levels in EVs. In our WMI model, 3DNA miRNA‐146b‐5p treatment significantly prevented microglial activation, hypomyelination, and cognitive defect induced by perinatal inflammation. Interpretations: These findings support that miRNA‐146b‐5p is a major regulator of microglia phenotype and could be targeted to reduce the incidence and the severity of perinatal brain injuries and their long‐term consequences. ANN NEUROL 2022;91:48–65